The role of brand silence and nostalgia in revitalizing traditional skincare products with advertising and celebrity endorsement strategy as a mediator - Vibhuti Tripathi; Tarunija Chandra (Journal of Business and Economic Studies (JBES), 2023)
The purpose of this research is to identify the role of brand salience and nostalgia in the revitalization of traditional skincare products present in India. The study also examines the mediating role of advertising and celebrity endorsement strategy on these relationships. Exploratory and confirmatory factor analysis was used to derive and validate the factors, and Hayes PROCESS Macro was used to assess direct-indirect-mediating relationships in SPSS 23. A total of 113 users of traditional antiseptic creams were undertaken via convenience sampling across India. Brand salience and nostalgia played a significant role in influencing customer perceived value and brand loyalty as outcomes of the revitalization of traditional skincare products. Advertising and celebrity endorsement strategy was found to have a significant mediating effect on these relationships. The study contributes to increase brand efficiency for revitalizing mature products in the skin care segment by developing and testing the relationship between different parameters. This study could help managers pay attention to various well-established but bygone brands in the personal care segment. The results would guide marketers to cope with the external challenges that the companies and their brands are facing.
Keywords: 330; Brand revitalization; Brand Salience; Nostalgia; Advertising and Celebrity Endorsement Strategy; Perceived Value; Brand Loyalty; Traditional Skincare products